Magnetron Sputtering a New Fabrication Method of Iron Based Biodegradable Implant Materials - Till Jurgeleit; Eckhard Quandt; Christiane Zamponi (Advances in Materials Science and Engineering)
It was shown in the previous decade that pure-iron has a large potential as a biodegradable medical implant material. It is necessary to tailor the material properties according to the intended use of the device. It is of great interest to investigate not only the influence of processing on the material properties but also alternative fabrication methods. In this work for the first time magnetron sputtering in combination with UV lithography was used to fabricate free standing, patterned pure-iron thick films. For the intended use as biodegradable implant material free standing thick films were characterized in terms of microstructure, degradation performance, and mechanical properties before and after various heat treatments. The influence of microstructural changes on the degradation behavior was determined by linear polarization measurements. The mechanical properties were characterized by tensile tests. Microstructure, surface, and composition were investigated by scanning transmission electron microscopy (STEM), energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) measurements. The foils exhibited a preferential orientation in 110 direction and a fine grained structure. Furthermore they showed a higher strength compared to cast iron and corrosion rates in the range of 0.1 mm/year. Their mechanical properties were tuned by grain coarsening resulting in a slight increase of the degradation rate.